The sintering temperature effect on the shrinkage behavior of cobalt chromium alloy - Kamardan, M.Ghazali; A. Zaidi, N. Hidayah; Dalimin, M. Noh; A. Zaidi, A. Mujahid; Jamaludin, S. Bahrin; A.Jamil, M.Mahadi (Science Publications, 2010)
Problem Statement: Co-Cr based alloys which is well known for its high Young’s modulus, fatigue strength, wear resistance and corrosion resistance is an important metallic biomaterial. However, till date there are only two type of Co-Cr alloy which are the castable and wrought cobalt alloy. Powder Metallurgy route for cobalt is expected to give better result of Co-Cr alloy. The purpose of this research was mainly to study the sintering temperature effect to the shrinkage behavior of Cobalt Chromium (Co-Cr) alloy of the powder metallurgy route. Approach: Co-Cr was produced following P/M route under sintering temperature of 1000, 1100, 1200, 1300 and 1400oC. The sintering time was fixed at 60 min. Several tests has been conducted to determine this effect such as the rate of shrinkage measurement, the bulk density and porosity percentage measurement, compression and hardness tests and micro structural study. Result: From the study, it was found that the sintering temperature has caused the shrinkage of Co-Cr. The increasing of the sintering temperature has caused to the increasing of shrinkage of Co-Cr. This has resulted to the reduction of the pore volume and hence increased it density. In conjunction to that, the strength and the hardness of Co-Cr was increased. Conclusion: Therefore, it is hope that it will bring new view of powder metallurgy Co-Cr alloy as bio-material.